Efficacy and safety of voretigene neparvovec (AAV2-hRPE65v2) in patients with RPE65-mediated inherited retinal dystrophy: a randomised, controlled, open-label, phase 3 trial. Issue 10097 (26th August 2017) - Russell, Stephen; Bennett, Jean; Wellman, Jennifer A; Chung, Daniel C; Yu, Zi-Fan; Tillman, Amy; Wittes, Janet; Pappas, Julie; Elci, Okan; McCague, Sarah; Cross, Dominique; Marshall, Kathleen A; et al.
Summary: Background: Phase 1 studies have shown potential benefit of gene replacement in RPE65 -mediated inherited retinal dystrophy. This phase 3 study assessed the efficacy and safety of voretigene neparvovec in participants whose inherited retinal dystrophy would otherwise progress to complete blindness. Methods: In this open-label, randomised, controlled phase 3 trial done at two sites in the USA, individuals aged 3 years or older with, in each eye, best corrected visual acuity of 20/60 or worse, or visual field less than 20 degrees in any meridian, or both, with confirmed genetic diagnosis of biallelic RPE65 mutations, sufficient viable retina, and ability to perform standardised multi-luminance mobility testing (MLMT) within the luminance range evaluated, were eligible. Participants were randomly assigned (2:1) to intervention or control using a permuted block design, stratified by age (<10 years and ≥10 years) and baseline mobility testing passing level (pass at ≥125 lux vs <125 lux). Graders assessing primary outcome were masked to treatment group. Intervention was bilateral, subretinal injection of 1·5 × 10 11 vector genomes of voretigene neparvovec in 0·3 mL total volume. The primary efficacy endpoint was 1-year change in MLMT performance, measuring functional vision at specified light levels. The intention-to-treat (ITT) and modified ITT populations were included in primary and safety analyses. This trial is registered withClinicalTrials.gov, numberNCT00999609, and enrolment is complete. Findings: Between Nov 15, 2012, and Nov 21, 2013, 31 individuals were enrolled and randomly assigned to intervention (n=21) or control (n=10). One participant from each group withdrew after consent, before intervention, leaving an mITT population of 20 intervention and nine control participants. At 1 year, mean bilateral MLMT change score was 1·8 (SD 1·1) light levels in the intervention group versus 0·2 (1·0) in the control group (difference of 1·6, 95% CI 0·72–2·41, p=0·0013). 13 (65%) of 20 intervention participants, but no control participants, passed MLMT at the lowest luminance level tested (1 lux), demonstrating maximum possible improvement. No product-related serious adverse events or deleterious immune responses occurred. Two intervention participants, one with a pre-existing complex seizure disorder and another who experienced oral surgery complications, had serious adverse events unrelated to study participation. Most ocular events were mild in severity. Interpretation: Voretigene neparvovec gene replacement improved functional vision in RPE65 -mediated inherited retinal dystrophy previously medically untreatable. Funding: Spark Therapeutics.